192k views
5 votes
Plz help me get the answe

Plz help me get the answe-example-1

2 Answers

3 votes

Answer:

b = 3

Explanation:


-7+(1)/(3)b=-6\qquad\text{add 7 to both sides}\\\\(1)/(3)b=1\qquad\text{multiply both sides by 3}\\\\3\!\!\!\!\diagup^1\cdot(1)/(3\!\!\!\!\diagup_1)b=(3)(1)\\\\b=3

User Alev
by
5.1k points
3 votes

Equation: -7+1/3 b=-6

Step 1. You need to simplify both sides of the equation.

1 /3 b−7=−6

Step 2: Add 7 to both sides. of the equation.

1 /3 b−7+7=−6+7

1 /3 b=1

Step 3: Then multiply both sides by 3.

3* ( 1 /3 b)=(3)*(1)

b=3

Answer: b=3

Hope I could help! :)

User Swidmann
by
7.5k points